Hypoparathyroidism following total thyroidectomy: high rates at a low-volume, non-parathyroid institution - Abood, Ali; Ovesen, Therese; Rolighed, Lars; Triponez, Frédéric; Vestergaard, Peter (Frontiers in Endocrinology, 2024)
Background: Hypoparathyroidism following total thyroidectomy is globally the most common complication to thyroid surgery. The reported complication rates vary widely and might be highly dependent on the surgical experience. In this study we aimed to evaluate the rate of hypoparathyroidism following primary total thyroidectomy at a low-volume institution that only performs thyroid surgery and does not have any experience with parathyroid surgery.Methods: Retrospective cohort study. All patients undergoing primary total thyroidectomy at the ENT-Department, Goedstrup Hospital, Denmark, over a 5-year period (2016-2020) were identified through the procedure codes for total thyroidectomy. Medical records, pathology reports, biochemical and medical histories were fully assessed for each patient. The primary endpoint was the rate of hypoparathyroidismboth immediate and permanent. Secondary outcomes were parathyroid gland identification rates, rates of parathyroid gland autotransplantation, and rates of inadvertent parathyroid gland excision.Results: A total of 89 patients were included in the final analysis. A total of 33 patients (37.1 %) experienced immediate hypoparathyroidism following surgery, while 30 patients (33.7 %) still were on active vitamin D two months postoperatively. One year following surgery, 28 patients (31.5 %) were still on active vitamin D and were considered as having permanent hypoparathyroidism. Sixty-one percent of the parathyroid glands were identified intraoperatively, and 19 % of the patients experienced parathyroid autotransplantation. Inadvertent parathyroid gland excision occurred for 21 % of the patients and was associated with a significantly increased risk of permanent hypoparathyroidism (RR = 2.99; 95 % CI: 1.36 -6.62, p = 0.005).Both transient and permanent hypoparathyroidism following total thyroidectomy at a lowvolume, non-parathyroid institution occurred with much higher frequencies than previously reported. The elevated rates were most likely due to the low-volume, non-parathyroid nature of the surgeons which in part was mirrored in low parathyroid gland identifications rates, and high rates of autotransplantation and inadvertent parathyroid gland excision.